Evaluación del uso del Ácido Ursodesoxicólico como tratamiento preventivo de la litiasis biliar. - Espinoza Vaca, Sara Sofia (2024)
The main objective of this research study was to evaluate the usefulness of Ursodeoxycholic Acid as a preventive treatment in biliary lithiasis, determining its effectiveness, possible adverse effects and its impact as part of preventive treatment. Ursodeoxycholic acid (UDCA) is produced in the liver of mammals, due to its chemical structure allows it to interact effectively with lipids and cholesterol, facilitating their digestive transport. Biliary lithiasis, influenced by factors such as sex, age and obesity, is highly prevalent in Latin America, with significant rates in indigenous populations and hospital emergencies in Ecuador. UDCA has been shown to be effective in dissolving gallstones, reducing hepatic cholesterol secretion and changing bile composition. The methodology was descriptive, retrospective and documentary, using a theoretical qualitative approach, analyzing scientific publications from the last five years, in Spanish and English, selected from databases such as PubMed and Scopus, applying specific inclusion and exclusion criteria. Twenty relevant references were used to generate new knowledge on the topic addressed. AUDC significantly improves hepatic biochemistry, preventing the formation of gallstones. It also reduces the incidence of sinusoidal obstruction syndrome in post-transplant patients and prevents cholesterol lithogenesis by altering biliary composition and gene expression. In addition, UDCA is effective in preventing gallbladder stones after bariatric surgery. Taken together, these studies underscore the value of UDCA as a therapeutic and preventive tool, improving clinical outcomes and patients' quality of life. This drug is highly effective in preventing gallstone formation, as well as well tolerated at doses of 600 mg daily or 8-10 mg/kg/day, not only prevents gallstones, but also significantly improves patients' quality of life, reducing the need for additional surgical interventions and improving overall well-being.